Varietal and harvesting stage variation in the content of carotenoids, ascorbic acid and tocopherols in the fruit of bitter gourd (Momordica charantia L.). Issue 3 (15th January 2016) - Dhillon, Narinder P. S.; Lin, Chung-Cheng; Sun, Zhanyong; Hanson, Peter M.; Ledesma, Dolores R.; Habicht, Sandra D.; Yang, Ray-Yu
Abstract : Bitter gourd ( Momordica charantia L.) is an important market vegetable in the tropics. The objectives of this study were to (1) conduct a preliminary evaluation of genetic diversity in bitter gourd flesh (without seeds) for phytonutrient (carotenoid, ascorbic acid and tocopherol) contents with the aim to understand which phytonutrients might be increased through breeding, (2) assess the association between fruit traits and phytonutrient contents and (3) evaluate the effect of the fruit harvest stage on phytonutrient contents. A total of 17 diverse bitter gourd entries of various commercial market types were evaluated for fruit traits and phytonutrient contents for 2 years. Significant differences ( P = 0.05) among the entries were detected for total carotenoids, total tocopherols, dry matter and fruit traits. Mean total carotenoid contents of the entries ranged from 10 to 1335 μg/100 g fresh weight in year 1 and 10 to 1185 μg/100 g fresh weight in year 2. Mean ascorbic acid contents were 69 and 61 mg/100 g fresh weight in year 1 and year 2, respectively. Total tocopherol contents among the entries ranged from 480 to 1345 and 445 to 2145 μg/100 g fresh weight in year 1 and year 2, respectively. Total carotenoid and ascorbic acid contents were highest at 12 days after fruit set (DAFS), but total tocopherol contents were highest from 14 to 20 DAFS. A 100 g portion of bitter gourd fruit can meet 190, 17 and 8% of the recommended daily allowances of vitamin C, vitamin E and vitamin A, respectively, for adults.